Disassembling Coal: Finance Capital, Environmental Law, and the Right to Information in South India. Issue 4 (21st January 2021) - Kumar, Mukul
Abstract: Since the liberalisation of India's energy sector began in the 1990s, the government has developed several novel techniques to make coal an attractive asset for investors. The pharaonic Ultra Mega Power Plant Project (UMPP) program is one such technique which secures finance capital, land, and environmental clearances for coal‐fired power plants. Drawing upon the analytic of assemblage, this paper tracks how the Cheyyur UMPP, one of the largest proposed coal‐fired power plants in the world, has been disassembled by a range of interdependent elements, from Right to Information (RTI) activism and environmental litigation to the perception of litigation risk and the materiality of coal. In pursuing an analysis of the events and elements which have led to the Cheyyur UMPP being disassembled, this paper calls for greater attention to the vulnerabilities, limits, and instabilities of coal assemblages.